2017
DOI: 10.18632/oncotarget.20129
|View full text |Cite
|
Sign up to set email alerts
|

Increased DCLK1 correlates with the malignant status and poor outcome in malignant tumors: a meta-analysis

Abstract: Doublecortin-like kinase 1 (DCLK1) has been found to be involved in malignant biological behavior of cancers and poor prognosis of cancer patients. The aim of this meta-analysis was to systematically clarify the relationships between expression level of DCLK1 and clinicopathological characteristics in tumors and assess its clinical value in cancer diagnosis and prognosis. 18 eligible studies with a total of 2660 patients were identified by searching the electronic bibliographic databases. Pooled results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
4
11
0
Order By: Relevance
“…Since the detection as a marker in cancer stem cells, DCLK1 has attracted attention of researchers from the field of oncology. Accumulating evidence indicates that DCLK1 expression is associated with advanced cancer stages and poor clinical prognosis [32] . Hence, whether or not DCLK1 directly drives cancers, DCLK1 is regarded as a critical biomarker in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Since the detection as a marker in cancer stem cells, DCLK1 has attracted attention of researchers from the field of oncology. Accumulating evidence indicates that DCLK1 expression is associated with advanced cancer stages and poor clinical prognosis [32] . Hence, whether or not DCLK1 directly drives cancers, DCLK1 is regarded as a critical biomarker in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, p62 seems to co-localize with Dclk1 as a punctate staining at the plasma membrane while occasional co-localization could be seen within the nucleus. Since Dclk1 exists in a membrane-bound long (Dclk1-L) and membrane/nuclear localized short (Dclk1-S) forms consistent with presence of both transcripts coded for by α- and β-promoters respectively [24], our findings suggest that both isoforms of Dclk1 are probably involved in the tumorigenic process. The increases in Dclk1-L and Dclk1-S promoter activities following treatment with either autophagy inhibitor CQ or LPS further support our conclusion.…”
Section: Discussionmentioning
confidence: 57%
“…Prior studies have shown that a subset of Dclk1-positive CSCs survive due to autophagy in response to curcumin [23] and that increased Dclk1 correlates with the malignant status and poor outcome in malignant tumors [24]. We next examined surgical samples from a patient with multiple tumors in the colon and metastasis to the liver.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Dclk1 was first described as a brain-specific gene, the roles of Dclk1 outside the nervous system have recently been the main area of study. Dclk1 is expressed in a variety of cancer cells [ 23 ], with a functional role in tumor growth and progression. However, its general role in carcinogenesis and clinical significance as a potential diagnostic marker remain unclear [ 24 ].…”
Section: Discussionmentioning
confidence: 99%